2019
DOI: 10.1097/gme.0000000000001326
|View full text |Cite
|
Sign up to set email alerts
|

The Kronos Early Estrogen Prevention Study (KEEPS): what have we learned?

Abstract: Objective:The Kronos Early Estrogen Prevention Study (KEEPS) was designed to address gaps in understanding the effects of timely menopausal hormone treatments (HT) on cardiovascular health and other effects of menopause after the premature termination of the Women's Health Initiative.Method:The KEEPS was a randomized, double-blinded, placebo-controlled trial to test the hypothesis that initiation of HT (oral conjugated equine estrogens [o-CEE] or transdermal 17β-estradiol [t-E2]) in healthy, recently postmenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 115 publications
(125 reference statements)
4
94
0
2
Order By: Relevance
“…The annual rate if cIMT increase was 0.007 mm, which corresponded to the results of previous studies conducted on early postmenopausal women of matching age [29][30][31]. In particular, in the KEEPS study, the annual rate of cIMT progression was also 0.007 mm [31]. In late postmenopausal women a significant cIMT progression was observed in the subgroup receiving placebo, but not phytoestrogens, the annual rate of cIMT progression was 0.019 and 0.011 mm, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The annual rate if cIMT increase was 0.007 mm, which corresponded to the results of previous studies conducted on early postmenopausal women of matching age [29][30][31]. In particular, in the KEEPS study, the annual rate of cIMT progression was also 0.007 mm [31]. In late postmenopausal women a significant cIMT progression was observed in the subgroup receiving placebo, but not phytoestrogens, the annual rate of cIMT progression was 0.019 and 0.011 mm, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The present study monitored the atherosclerosis progression in early postmenopausal women receiving the treatment with phytoestrogen preparation or placebo and found no significant increase of cIMT during the 2-year follow up. The annual rate if cIMT increase was 0.007 mm, which corresponded to the results of previous studies conducted on early postmenopausal women of matching age [29][30][31]. In particular, in the KEEPS study, the annual rate of cIMT progression was also 0.007 mm [31].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both the WHI and WEST trials of estrogen supplementation led to increased mortality in post-menopausal women (6, 7), although issues with trial design, including the dose, type and timing of estrogen supplementation were raised. The Kronos Early Estrogen Prevention Study (KEEPS) study found that neither oral nor transdermal estrogens affected the progression of atherosclerosis (measured as CIMT, carotid-artery intima-media thickness), when given to recently postmenopausal women (21). On the other hand, Early versus Late Intervention Trial with Estradiol (ELITE) found that oral estradiol therapy (when initiated within 6 years of menopause) was associated with less progression of subclinical atherosclerosis (measured as CIMT) (22).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid profile abnormalities and additional metabolic changes (obesity, arterial hypertension, and insulin resistance) lead to increased risk of cardiovascular events [64]. Despite the change in lipid profile that is attributed to ovarian failure, hormone replacement therapy with oestrogen and progesterone has not reduced the cardiovascular risk and markers of subclinical atherosclerosis in postmenopausal women [65]; nowadays it is not recommended in cardiovascular prevention but merely for symptomatic relief. Therefore, in postmenopausal women with abnormal lipid profile a targeted hypolipidemic therapy (e.g.…”
Section: Hypogonadismmentioning
confidence: 99%